Nachruf auf P. Prof. Dr. Ulrich Horst OP - Mandrella, Isabelle (Münchener theologische Zeitschrift, 2025)
The article "Obituary for P. Prof. Dr. Ulrich Horst OP" in the Munich Theological Journal honors the life and work of P. Prof. Dr. Ulrich Horst OP, a renowned theologian and professor of the history of theology at Ludwig-Maximilians-University Munich. Horst was an expert in medieval theology and the history of dogma, particularly in the areas of ecclesiology and the history of his order, the Dominicans. He passed away on December 9, 2024, and was buried at the Ohlsdorf Cemetery in Hamburg. His legacy is upheld by the Catholic Theological Faculty and the Martin-Grabmann Research Institute in Munich.